Genes, autoimmunity and pathogenesis of rheumatic heart disease - Guilherme L; Köhler K; Postol E; Kalil J (Wolters Kluwer Medknow Publications, 2011)
Pathogenesis of rheumatic heart disease (RHD) remains incompletely understood. Several genes associated with RHD have been described; most of these are involved with immune responses. Single nucleotide polymorphisms in a number of genes affect patients with RHD compared to controls. Molecular mimicry between streptococcal antigens and human proteins, including cardiac myosin epitopes, vimentin and other intracellular proteins is central to the pathogenesis of RHD. Autoreactive T cells migrate from the peripheral blood to the heart and proliferate in the valves in response to stimulation with specific cytokines. The types of cells involved in the inflammation as well as different cytokine profiles in these patients are being investigated. High TNF alpha, interferon gamma, and low IL4 are found in the rheumatic valve suggesting an imbalance between Th1 and Th2 cytokines and probably contributing to the progressive and permanent valve damage. Animal model of ARF in the Lewis rat may further contribute towards understanding the ARF.